Никоний в античных письменных источниках - Охотников, С.Б. (Материалы по археологии Северного Причерноморья, 2015)
The settlement under such name is mentioned in texts of several ancient authors and in two inscriptions on stones. Ps.-Scyl., 68; Ptol., III, 10,8; ps.-Arr., 87 use the spelling Nikonion, while Strabo, VI, 3, 16 and Steph. Byz. Ethn. call it Nikonia. The inscription found in Tyras names it Nikoneon. There are some more variants, which come, probably, from misreading and writing errors in various copies of texts and on medieval maps. The proper names and names of geographical places are transcribed in Russian in various ways. So we suggest choosing a variance which is most widely applied recently – “город Никоний” – “ΠΟΛΙΣ ΝΙΚΟΝΙÙΝ” – “city Nikonion.”